Predominance of DENV-3 among patients in Ouagadougou, Burkina Faso - Abdoul Karim Ouattara; Shoukrat Ohuwa Toyin Bello; Alphonsine Ouédraogo; Lassina Traoré; Florencia Wendkuuni Djigma; Jacques Simporé (Journal of Vector Borne Diseases)
Background & objectives: Dengue is an emerging vector-borne viral disease in tropical and subtropical areas such as Burkina Faso that experienced dengue outbreak in, 2013, 2016, 2017 and more recently in 2023. This study aimed to determine the seroprevalence and dengue serotype in suspected patients in Ouagadougou, Burkina Faso. Methods: The study was conducted during October and November 2023 and included suspected febrile patients seen at HOSCO and CERBA. Plasma or serum samples were used for the detection of non-structural proteins (NS1) and IgM and IgG antibodies against the dengue virus using SD Bioline Dengue Duo rapid detection kit. Viral RNA was extracted using the QIAamp Viral RNA Mini Kit and dengue serotypes were determined by real-time RT-PCR using the Dengue Real-TM Genotype kit. Results: The study population consisted of 896 patients, including 397 (44.3%) men and 499 (55.7%) women. Dengue seroprevalence was 16.5% (148/896) with 14.1% (126/896) of patients positive for the NS1 antigen, 1.3% (12/896) positive for IgM, and 2.7% (24/896) positive for IgG. Serotyping among 40 out of 45 positive patients revealed 77.5% (31/40) DENV-3, 17.5% (7/40) DENV-1, and 5.0% (2/40) DENV-2. Interpretation & conclusion: The present study reports a high seroprevalence of dengue virus infection among patients during the months considered as the peak of infection in Burkina Faso. The results revealed a predominance of DENV-3. Continuous surveillance of dengue virus serotypes circulating in Burkina Faso is crucial.